Interrogating the theological argument for the reality of God within African religious milieu (2014)
Empirical philosophers, down the ages have argued against the existence of God, employing the use of reason as a premise for establishing their argument. This exercise resulted in atheism – the belief that there is no God. While some atheists maintain that God never existed in the past, there are others who contend that he existed but is now dead. Hence, Anselm's theism and other arguments for God's existence pervaded the academic spectrum. This paper, therefore, establishes the manifestation of theistic arguments within the religious context in Africa. Furthermore, the paper concludes by debunking the misrepresentation of African ideas of God whom some sit-at-home writers described as Deus absconditus or Deus remotus.